Using Wikipedia Assignments to Teach Critical Thinking and Scientific Writing in STEM Courses - Gareis, Jolie A. L.; Larson, Erin I.; Ardón, Marcelo; Berges, John A.; Brandt, Jessica E.; Busch, Kaitlyn M.; Chraibi, Victoria L. S.; Gallagher, Elizabeth N.; Hondula, Kelly L.; Kincaid, Dustin W.; Levine, Todd D.; Little, Chelsea J.; et al. (Frontiers in Education, 2022)
While many instructors have reservations against Wikipedia use in academic settings, editing Wikipedia teaches students valuable writing, editing, and critical thinking skills. Wikipedia assignments align with the community of inquiry framework, which focuses on the elements needed for a successful online learning experience. We report on a faculty mentoring network, created by WikiProject Limnology and Oceanography, which helped 14 instructors with little to no prior experience implement a Wikipedia assignment in their classes. We found that Wikipedia assignments increase students’ motivation to produce high quality work and enhance their awareness of reliable scientific sources. Wikipedia assignments can be comparable to other writing assignments in length and complexity, but have a far wider audience than a traditional research paper. Participants in our mentoring network reported challenges with implementing this new type of assignment, and here, we share resources and solutions to those reported barriers.